Role of rapid response factors to injuries in basketball players studying at russian universities - Ma Kehan,; Makeeva V.S. ,; Shirokova E.A. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify factors that have a significant impact on student basketball players making emergency decisions when injuries occur. Methods and structure of the study. During the analysis of scientific and methodological literature, 4 management factors of rapid response to injuries among basketball players classified as the first level were identified. In turn, each of the factors (university administration, coach, athlete, parents) is characterized by different types of management decisions in the event of injuries that were classified as the second level. The experts were asked to rate the importance of each first-level factor on a scale from 1 to 5 (1 – insignificant, 5 – very important). Results and conclusions. Coach level and athlete level were found to be the most important, followed by university and parent levels. Therefore, the main efforts aimed at preventing injuries must be implemented at the level of athletes and coaches. First of all, they should be aimed at increasing the awareness of athletes and coaches in the means and methods of preventing emergency situations, as well as ensuring the neuropsychic stability that is necessary when making decisions if they arise.